High-technology safety construction vest / Wan Muhammad Arif Safwan Wan Aziz and Ida Nianti Mohd Zin - Wan Aziz, Wan Muhammad Arif Safwan; Mohd Zin, Ida Nianti (2023)
Construction is one of the most dangerous economic industries in the world. Unsafe practices, involvement of people, dangerous machinery, poor job site conditions, poor management, and peculiarities of the sector are some of the major causes of accidents on construction sites. It is widely acknowledged that Personal Protective Equipment (PPE) effectiveness serves as a crucial safeguard for workers’ safety and well-being. The absence of PPE is a challenge for the sector. Construction site employees are the primary group affected by safety and health concerns. Monitoring the on-site personnel’s health issues is necessary. The issue with thermal comfort comes next. A safety vest needs to be cosy no matter the circumstance. Due to climate change, there is a substantial risk of heat stress among construction workers all around the world. For the convenience of construction workers, there is a need to resolve these urgent difficulties.